2017
DOI: 10.3390/su9101696
|View full text |Cite
|
Sign up to set email alerts
|

Normative Beliefs, Attitudes, and Social Norms: People Reduce Waste as an Index of Social Relationships When Spending Leisure Time

Abstract: Abstract:This study has adopted and refined Ajzen's theory of planned behavior, theory of reasoned action, and the value-belief-norm theory by Stern et al. to investigate the effects of normative beliefs, attitudes, and social norms on pro-environmental behavioral intentions. A total of 391 valid responses were collected from visitors to a theme park in Taiwan. A structure equation analysis indicated that the overall fit of the proposed model was supported. It was also found that both attitudes and social norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 61 publications
5
79
0
4
Order By: Relevance
“…However, the present study uses only one component, 'attitude', to predict 'intention' based on the objectives of the study. The partial adoption of the TPB in other research papers can also be found [64,65]. The TPB is operationalized by exploring the 'attitudes' of stock market investors regarding ESG issues, and thus focusing on the 'intention' towards ESG investing with the consideration of investment decision.…”
Section: Theoretical Underpinningmentioning
confidence: 99%
“…However, the present study uses only one component, 'attitude', to predict 'intention' based on the objectives of the study. The partial adoption of the TPB in other research papers can also be found [64,65]. The TPB is operationalized by exploring the 'attitudes' of stock market investors regarding ESG issues, and thus focusing on the 'intention' towards ESG investing with the consideration of investment decision.…”
Section: Theoretical Underpinningmentioning
confidence: 99%
“…[45] find that even though environmental concerns are directly related to attitudes, egoistic concerns are the strongest predictor of attitudes. In the same line, [46] state that environmental education can assist in fostering pro-environmental behaviour, but this alone is not enough. In their case, social norms have a stronger influence on behavioural intentions than attitudes.…”
Section: The Theory Of Planned Behaviourmentioning
confidence: 99%
“…Further research is required to provide comparisons between Taiwan and other countries and to determine related similarities or differences. In addition, future research can also be conducted to investigate other factors that influence pro-environmental behaviors [56,57], the related issues in the implementation of policies by public servants, and other possible effects on behavioral paths. Strongly Disagree Disagree Neutral Agree Strongly Agree I have an obligation to cherish the limited resources of the earth.…”
Section: Implications Limitations and Future Researchmentioning
confidence: 99%